Sexual murderers: psychological and criminological factors in diverse types - Higgs, Tamsin (2017)
Studies of sexual murder are abundant, but an empirically supported understanding of this type of crime and its perpetrators is limited in important ways. The overall aim of this thesis was to work towards a theoretical model recognising that sexual murder is a heterogeneous concept. Also, the thesis aimed to understand sexual murder in the wider context of sexual aggression against adult women. First, a systematic review was conducted to clarify the existing typologies of sexual murder. Three consistently observed subtypes were found. These were labelled sexualised murder, grievance murder, and rape murder. A behaviour that could be used to differentiate groups was post mortem sexual interference (PMSI), indicative of sexualised murder. Subsequently, a study was conducted comparing subgroups of sexual murderers (those who had engaged in PMSI, and those who had not), and rapists, on developmental factors, adult lifestyle, and criminal career. The main finding was that the groups responded differently to early adversity. Difficulties with social and sexual relationships leading to the development of sadistic interests, as opposed to pervasive antisociality, distinguished PMSI sexual murderers from rapists, while non-PMSI sexual murderers were largely similar to rapists. However, although the role of psychopathy in sexual aggression is debated, no group was strongly characterised by psychopathy in the present study. A secondary study was conducted to verify that this finding was not associated with limitations in the assessment tool used (the Psychopathy Checklist: Screening Version [PCL: SV]; Hart, Cox, & Hare, 1995). Good psychometric properties were found. Next, a case study demonstrated the functional heterogeneity of the act of killing under the broadly defined term ‘sexual murder’, and highlighted the importance of this in forensic case formulation and intervention. Finally, drawing on the findings of the present research, a new model of sexual murder is proposed to address some of the issues discussed in this thesis.